Urban high school faculty members speak up: what they need from a school counseling program from school counselors and principals - Graf, Eric; Yavuz, Olcay (Journal of Educational Leadership and Policy Studies, 2023)
There is a growing emphasis to improve every student's academic, social-emotional, and career and college development as schools strive to design and deliver comprehensive counseling programs that support students' development in these areas. The purpose of this study is to explore a large urban high school teachers' counselors and admins' perspectives on improving a high-poverty urban school's counseling services to extend school leaders' and counselors' knowledge about delivering effective school counseling programs as, ultimately, success lies with an effective principal and school counselor partnership. Particularly, data from our study will allow urban school principals and school counselors to identify the high and low program needs of urban students to become college, career, and life ready. The next set of comparisons was conducted for social-emotional needs. Like academic development needs, the entire ANOVA summary tables showed non-significant differences. The findings indicated that some responses varied significantly across (1) special education faculty, (2) regular classroom teachers and (3) school counselors in terms of rating of students' counseling needs. School leaders and school counselors can apply the findings of this study to create systemic and comprehensive student services in their schools. Particularly, school leaders and counselors can apply the results in decision-making, discussions, and time allocation in prevention/education versus reactive/responsive academic and counseling services.
Keywords: Administrator Attitudes; Administrator Role; Career Readiness; College Readiness; Connecticut; Counselor Attitudes; Counselor Role; Educational Needs; High School Teachers; Poverty; Principals; School Counseling; School Counselors; Social Emotional Learning; Student Needs; Teacher Attitudes; Urban Schools; dept.edl

Higher education and the great resignation: a crisis of compounded inequities - Rivers, Yevgeniya (2023)
Keywords: SCSU-student; dept.edl

Self-Identification in Black, Red, Brown, and White: A clarion call to address medical racism in Native American communities - Boudreaux, Mary (Navigating Academia During COVID-19: Perspectives and Strategies from BIPOC Women, 2023)
This chapter provides a brief autobiographical account of her multiethnic and racial background as a Louisiana Creole in south Louisiana. The author points out that among all racial and ethnic groups in the United States, Indigenous people are the only ones that require some form of lineal Native American descent or blood quantum. The chapter provides an ancestry account of two American Indian tribes along the bayous of south Louisiana, the Chitimacha, and the United Houma Nation. While one federally recognized tribe has attempted to remove all relations to individuals of Black, Negro, or African American descent, the other has closed enrollment to new members (despite lineal descent), with the unifying factor among these communities being establishing progenitors. Finally, the author articulates how lack of access to resources related to issues such as COVID-19 has perpetuated the historical legacy of medical racism in tribal and underserved communities in the United States.
Keywords: COVID-19; Medical racism; Native American; Tribal communities; dept.edl